Conductivity at Low Humidity of Materials Derived from Ferroxane Particles - Alberto Lapina; Peter Holtappels; Mogens Mogensen (International Journal of Electrochemistry)
Carboxylic-acid-stabilised γ-FeOOH particles (ferroxanes) are synthesized using a precipitation from aqueous solution, and a following reaction with acetic acid. The materials produced with these powders are investigated by XRD, SEM, nitrogen adsorption-desorption, and impedance spectroscopy. Conductivity of both sintered and unsintered materials decreases strongly with a decrease in water partial pressure in the atmosphere during the test. The highest conductivity (7·10−3 S cm−1) is measured in air (pH2O = 0.037 atm) at room temperature on sintered material. The conductivity values are compared with other works in the literature and the dependence of conductivity on surface area and pore size is discussed. It is suggested that both unsintered and sintered materials act as proton conductors at room temperature under moderate humidity conditions.